(3GdHjGf Yf GNJdGa CFeI GdCeUGQ hEJaGbge aj YOO Bi GdbQBf heG jfJXe HPdc ef GdCHhGHs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj, J (B444 (3g` s
(3ChdgG (B:s
(3bGd CHh YeQh GdMeO ddg GdPi NTYJ dg GdCUhGJ , hbUQJ Yfg GdUaGJ , hNVYJ dg GdQbGH , hPdJ dg GdUYGH s
(3BNQgG (B:s
(3bGd SeYJ GHf CHj HRI bGd Cedi Ydi CHj bGd bGd CHh YeQh agPG eHdZ LgOfG ajeG CaQOfG dg cJGHfG Je GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjIs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
Keywords: (3GdbQGAGJ hGdJLhjOs